Synthesis, Spectral and Thermal Studies on Lanthanum(III) Complexes of Piperidin-4-ones - Selvaraj, Kuppusamy; Theivarasu, Chinniagounder (Asian Journal of Chemistry, 2016)
The diamagnetic lanthanum(III) nitrate (La1–La10) and chloride (La11–La20) complexes of piperidin-4-ones (L1–L10) of general formula [La(L)2(NO3)3(H2O)2] and [La(L)Cl3(H2O)2] have been prepared and characterized by various physico-chemical studies like elemental analysis, molecular weight determination, molar conductance, thermal and spectral studies. Molar conductance data indicate that these complexes are non-electrolytes. IR spectral data show the presence of water molecules and thermal studies confirm that these water molecules are coordinated. IR spectra also reveal that the nitrate groups are coordinated to the metal ion as bidentate ligands. IR and NMR spectral studies suggest that piperidin-4-ones coordinate with metal ions only through ring nitrogen and not through carbonyl group.